2020
DOI: 10.1177/1120672120962054
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines, oxidative and antioxidative stress levels in patients with diabetic macular edema and hyperreflective spots

Abstract: Purpose: To determine the levels of serum oxidative, antioxidative markers and inflammatory cytokines in patients diagnosed with diabetic macular edema (DME) whose hyperreflective spots (HRS) were detected by optical coherence tomography (OCT). Methods: In this prospective cross-sectional clinical study included a total of 88 patients; 31 patients (group-1) with DME and HRS detected by OCT, 29 patients (group-2) with DME without HRS, and 28 patients (group-3) diagnosed with diabetes mellitus (DM) without any d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Due to inflammation and oxidative stress, DRT leads to the impairment of the outer retinal barrier, causing increased vascular permeability (30). The hyperreflective spots observed on OCT may be the activated microglia, which are associated with a severe inflammatory response (7,27). These findings all suggest a close association between DME and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to inflammation and oxidative stress, DRT leads to the impairment of the outer retinal barrier, causing increased vascular permeability (30). The hyperreflective spots observed on OCT may be the activated microglia, which are associated with a severe inflammatory response (7,27). These findings all suggest a close association between DME and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical trials have shown that approximately 40% of patients are non-responsive to anti-VEGFs (6). While more recent research suggests that inflammatory factors play key roles in the development of DME (7,8). Increased levels of inflammatory mediators may lead to early and sustained chronic inflammation of diabetic retina, leukocyte activation, adhesion to vascular endothelium, disruption of blood retinal barrier, increased vascular permeability, and eventually macular edema.…”
Section: Original Articlementioning
confidence: 99%
“…Previous research has looked into the role of oxidative stress in the progression of DR. It is also stated that oxidative stress increases as a result of duration of DM, overweight/obesity and central obesity, and lower HDL cholesterol and TG:HDL ratio, and accordingly affects the development of DR. [61][62][63]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that patients with DME have increased levels of proinflammatory mediators in aqueous humor com-pared to non-DME cases [8], while there is a controversy whether the pathophysiology of DME is mainly attributed to such systemic affection or to a local intraocular response. Of note, several studies have shown that elevated serum lipids, including cholesterol and low-density lipoprotein (LDL), demonstrated a significant association with retinal hard exudates and formation of DME [9][10][11][12], while elevated IL-6 has also been correlated with diffuse retinal thickness or severity of DME [13,14].…”
Section: Introductionmentioning
confidence: 99%